Silom Area's Transformation through LGBTQ+ Community Hub in Bangkok Metropolis - Chitchakkol (Zenodo (CERN European Organization for Nuclear Research), 2025)
Silom has been a dynamic urban area in Bangkok, evolved through physical, economic, and social transformations, particularly as a central LGBTQ+ hub. This research objective is to analyze the community district evolution of LGBTQ+ group in the Silom area, Bangkok Metropolis. Across six historical periods, from its early development to the present. A qualitative research methodology was employed, incorporating field observations, in-depth interviews, and document analysis. Results reveal that Silom's physical and social structures have played crucial roles in sustaining the LGBTQ+ community, providing spaces that foster social interactions and identity expression. Additionally, urban policies, mass transit expansions, and economic growth have influenced its role as an LGBTQ+ hub. However, ongoing commercialization and economic shifts pose challenges to maintaining its unique identity. This study highlights the need for balanced urban development policies that preserve Silom's historical and cultural significance while accommodating modernization and economic progress.
Keywords: Southeast Asian Sociopolitical Studies; Urban Planning and Governance; Socioeconomic Development in Asia